Konsep Pendidikan Islam Pada Remaja di Era Disrupsi Dalam Mengatasi Krisis Moral - Burhan Nudin (Universitas Alma Ata, 2020)
The development of technology and globalization directly or directly can affect the moral development of adolescents in the millennial era. In the millennial era humans began to abandon the conventional ways of living their lives and were replaced by lifestyles. Today's modernization lifestyle which is a trend has a positive impact as well as a very large negative impact. The aims of this study are to determine Islamic education role in children, especially among adolescents, to overcome the moral crisis that is happening in society. This study uses descriptive analytical method to discuss the subject with the Library Research technique. The results indicate that religious education has a central role in tackling and preventing moral decline in adolescents in the disruption era. Changes in the teaching approach and the concept of education must be changed to keep pace with the times. The concept of religious teaching must be shifted, namely by utilizing developing technology and increasing the propagation institutions such as TPA and Majelis Ta'lim around the community and the condition that is as per the way of life of every locale.